2017
DOI: 10.3892/mmr.2017.7246
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of cannabinoid receptor type 1 and CB2 cannabinoid receptors, and transient receptor potential vanilloid channels in pterygium

Abstract: Cannabinoids, as multi-target mediators, activate cannabinoid receptors and transient receptor potential vanilloid (TRPV) channels. There is evidence to support a functional interaction of cannabinoid receptors and TRPV channels when they are coexpressed. Human conjunctiva demonstrates widespread cannabinoid receptor type 1 (CB1), CB2 and TRPV channel localization. The aim of the present study was to investigate the expression profile for cannabinoid receptors (CB1 and CB2) and TRPV channels in pterygium, an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
0
9
1
Order By: Relevance
“…A study indicated a reduction of TRPV1, TRPV2, and TRPV4 expression levels and an increased level of TRPV3 expression in epithelium of a primary pterygium as compared with normal conjunctival. [ 17 ] The findings in the pterygial epithelium were not identical to our data, although the exact reason, for example, racial difference, is to be explored. These authors report that the expression of TRPV3 was more marked in the pterygial epithelium as compared with a healthy conjunctival epithelium that coincides with our data.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…A study indicated a reduction of TRPV1, TRPV2, and TRPV4 expression levels and an increased level of TRPV3 expression in epithelium of a primary pterygium as compared with normal conjunctival. [ 17 ] The findings in the pterygial epithelium were not identical to our data, although the exact reason, for example, racial difference, is to be explored. These authors report that the expression of TRPV3 was more marked in the pterygial epithelium as compared with a healthy conjunctival epithelium that coincides with our data.…”
Section: Discussioncontrasting
confidence: 89%
“…This tissue is composed of stratified epithelium and stroma and an innermost endothelial single-cell layer. [ 12 13 14 15 16 ] Although the expression pattern of TRP family members in healthy cornea and conjunctiva as well as pterygium was described,[ 17 18 ] there are no available reports describing their expression pattern in ocular surface neoplastic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Control slides were invariably negative for immunostaining. Renal tissue was used as positive control for TRPV1, TRPV3, and TRPV4 antibodies and ophthalmic pterygium for TRPV2 antibody [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Assimakopoulou et al described an intense immunostaining for CB1r and CB2r in all tissue layers of human pterygium, in a case series including 32 eyes of 32 patients. In particular, they described a strong and moderate granular cytoplasmic immunoreactivity for CB1r and CB2r in the basal and suprabasal layers, respectively [ 25 ].…”
Section: Cannabinoid Receptorsmentioning
confidence: 99%